2014
DOI: 10.14687/ijhs.v11i2.3036
|View full text |Cite
|
Sign up to set email alerts
|

Humiliation in the virtual world: Definitions and conceptualization

Abstract: The cyberspace represents a platform for social relations which permit to be in touch with the World, to be "seen" by others and to "see" others. As new technologies emerge, ways of viewing are revised, especially through screens: though it has facilitated communication, the main innovation of the virtual world has been seeing, hearing and showing everything with the individual at the center of permanent interactions. But this overexposure can be dangerous: in attempting to be as much a part of the virtual wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…One of the consequences of adolescence is that, as the number of settings in which adolescents engage with peers, while the social surroundings increase and become more complex, so do the contexts in which they experience peer victimization. As social media becomes more accessible and relied upon, nurturing real-life self-concepts becomes inadequate, while more adolescents find personal popularity and value in the virtual space a necessity (Dilmac, 2014). The pressure and fear of “missing out” on social interactions becomes omnipresent.…”
Section: Introductionmentioning
confidence: 99%
“…One of the consequences of adolescence is that, as the number of settings in which adolescents engage with peers, while the social surroundings increase and become more complex, so do the contexts in which they experience peer victimization. As social media becomes more accessible and relied upon, nurturing real-life self-concepts becomes inadequate, while more adolescents find personal popularity and value in the virtual space a necessity (Dilmac, 2014). The pressure and fear of “missing out” on social interactions becomes omnipresent.…”
Section: Introductionmentioning
confidence: 99%
“…Although shaming is perceived as a negative act, Aharoni (2020) distinguishes between shaming as a means (shaming motivated by a desire to expose a non-normative social phenomenon, such as sexual abuse, and to encourage social change) and shaming as a goal (motivated by the desire to hurt someone, for example as an act of revenge). Interestingly, the privacy concerns of shamed children are not necessarily about the intrusion, seclusion or disclosure of embarrassing information, but rather, about the disruption in their ability to continue to participate in online spaces free from attacks (Dilmac, 2014). Recently, Shenton (2020) analyzed contemporary social media and suggested that public online shaming is also an antagonistic “poetic” practice through which users forge their identities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Além disso, jovens com características relacionadas a autossacrifício podem ser percebidos pelos demais como um "alvo fácil" para agressões, que não irão se defender devido a suas dificuldades em se posicionar e impor limites. Por outro lado, o cyberbullying constitui-se em uma forma de demonstrar poder e subjugar o outro (Dilmaç, 2014;Smith et al, 2013) O esquema de Grandiosidade está relacionado à percepção de que se é superior ou especial, de modo que a pessoa compreende que não está sujeita às mesmas regras que os demais (Young et al, 2003). O fato de vítimas-agressores terem apresentado maiores escores nesse esquema pode indicar que a realização de cyber agressão esteja vinculada à crença de que são melhores e mais espertos e, por isso, podem agir da forma que quiserem (Calvete, 2008).…”
Section: Tabelaunclassified